Differential Outcomes and Clinical Challenges of NAFLD With Extreme Obesity. Issue 10 (21st July 2020) - Arnouk, Joud; Rachakonda, Vikrant P.; Jaiyeola, Diana; Behari, Jaideep
Abstract : Nonalcoholic fatty liver disease (NAFLD) is closely associated with obesity. The prevalence of extreme obesity, defined as body mass index (BMI) of 50 kg/m 2 or higher, is rising more rapidly than overall obesity. We aimed to compare the clinical outcomes and performance of noninvasive fibrosis assessment tools in NAFLD with or without extreme obesity. A retrospective analysis was performed in 304 patients with NAFLD with extreme obesity and compared them to patients with NAFLD with BMI of 40 kg/m 2 or less, matched for age, gender, race, and liver fibrosis stage. The mean age of the NAFLD with extreme obesity cohort was 55.9 years, BMI 55 kg/m 2, and 49.7% had cirrhosis at initial evaluation. Baseline cirrhosis and coronary artery disease were associated with increased risk of death, and dyslipidemia with decreased risk of mortality. Age, insulin use, hypertension, albumin and platelet count were associated with cirrhosis. Fifteen percent of patients had weight‐loss surgery, but this was not associated with survival or risk of cirrhosis. Of the 850 abdominal ultrasound scans performed in 255 patients, 24.1% were deemed suboptimal for hepatocellular carcinoma screening. The mean NAFLD fibrosis score (NFS) in the extreme obesity cohort, versus a propensity‐matched cohort with BMI of 40 kg/m 2 or less, was significantly different for both low fibrosis (F0‐F2) (0.222 vs. −1.682, P  < 0.0001) and high fibrosis (F3‐F4) (2.216 vs. 0.557, P  < 0.001). Conclusion: NAFLD with extreme obesity is associated with increased risk of liver‐related and overall mortality. Accurate noninvasive assessment of liver fibrosis, low rates of weight loss surgery, and high failure rate of ultrasound were identified as clinical challenges in this population. Abstract : Management of NAFLD with extreme obesity (BMI ≥ 50 kg/m 2 ) is challenging. Cirrhosis at initial diagnosis is present in 50%, and a significant percentage of ultrasound scans for HCC surveillance are nondiagnostic in this population. Optimum cutoffs of NAFLD fibrosis score for noninvasive fibrosis assessment are markedly different than in patients with BMI of 40 kg/m 2 or less.